2010
DOI: 10.1590/s0066-782x2010005000112
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomiopatia chagásica: prognóstico no perfil clínico-hemodinâmico C

Abstract: Background: Patients with heart failure (HF) who are admitted showing poor perfusion and congestion (clinicalhemodynamic profile C) are the group that evolves with the worst prognosis in decompensated heart failure. However, there is little information in literature on the etiology of cardiopathy influences the outcome of patients in advanced stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
3
Order By: Relevance
“…9 In our study, the average age of chagasic patients was not significantly lower than that of non-chagasic patients. Some studies have shown an average age that is even lower in the chagasic group as a result of the pathogen- esis of the disease, such as the study by Cardoso et al, 10 which found an average age of 53 years.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…9 In our study, the average age of chagasic patients was not significantly lower than that of non-chagasic patients. Some studies have shown an average age that is even lower in the chagasic group as a result of the pathogen- esis of the disease, such as the study by Cardoso et al, 10 which found an average age of 53 years.…”
Section: Discussionmentioning
confidence: 97%
“…Cardoso et al 10 conducted a cohort study that assessed patients with clinical hemodynamic profile C, according to the classification given by Stevenson. Systolic blood pressure (SBP) was compared in chagasic and non-chagasic patients, resulting in 89.3±17.1 mmHg versus 98.8±21.7 mmHg (p=0.03).…”
Section: Discussionmentioning
confidence: 99%
“…However, CHD has a specific autonomic imbalance, a different pattern of myocardial fibrosis associated with an inflammatory milieu generated by parasite and host defenses, an increased risk of complex arrhythmias and a known worse prognosis than cardiomyopathies from other etiologies [42, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients who are typically hospitalized in our medical facility are those with severe advanced heart failure in a decompensation period that does not respond to initial therapy; frequently, these patients present with low cardiac output (10). In our service, dobutamine is preferred over milrinone.…”
Section: And Methodsmentioning
confidence: 99%